Structure–function analysis of the ER-peroxisome contact site protein Pex32 - Wu, Fei; van der Klei, Ida J. (Frontiers in Cell and Developmental Biology, 2022)
In the yeast Hansenula polymorpha the ER protein Pex32 is required for associating peroxisomes to the ER. Here, we report on a structure-function analysis of Pex32. Localization studies of various Pex32 truncations showed that the N-terminal transmembrane domain of Pex32 is responsible for sorting. Moreover, this part of the protein is sufficient for the function of Pex32 in peroxisome biogenesis. The C-terminal DysF domain is required for concentrating Pex32 at ER-peroxisome contact sites and has the ability to bind to peroxisomes. In order to better understand the role of Pex32 in peroxisome biogenesis, we analyzed various peroxisomal proteins in pex32 cells. This revealed that Pex11 levels are strongly reduced in pex32 cells. This may explain the strong reduction in peroxisome numbers in pex32 cells, which also occurs in cells lacking Pex11.